Highly-conductive porous poly(ether ether ketone) electrolyte membranes for flexible electrochromic devices with variable infrared emittance. (1st February 2020) - Li, Xiaobai; Zhang, Leipeng; Wang, Bo; Xu, Gaoping; Yu, Shuang; Pan, Mengyao; Dou, Shuliang; Li, Yao; Zhao, Jiupeng
Abstract: Electrolytes with superior ion conductivity are highly demanded for infrared variable emittance devices (IR-VEDs) to realize fast response time and good IR emittance modulation ability. Herein, a poly(ether ether ketone) (PEEK) membrane featured by well-connected pore structure and high porosity is proposed for the first time as the electrolyte material for the IR-VEDs. In contrast to the conventionally used gel electrolytes, the newly designed porous PEEK membrane is capable of obtaining high liquid electrolyte loading while maintaining good membrane integrity, resulting in high conductivity (6.8 × 10 −3 S cm −1 ) and simple device assembly process. Flexible IR-VEDs have been fabricated by employing polyaniline films deposited on porous Au electrode as the IR regulation layer. By controlling the loading of liquid electrolyte in porous electrode, continuously high-speed ion transfer channels could be constructed between the PEEK electrolyte membrane and the Au electrode in the devices taking advantage of their porous structure. The resultant IR-VED exhibits an excellent overall performance integrating superior IR emittance adjustment ability (the emittance change in the wavelength range of 2.5–25 μm is 0.47), fast switching time (<10 s) and good cycling stability, indicating promising applications in dynamic thermal control fields. Highlights: A PEEK membrane with high porosity was proposed as the electrolyte for IR-VEDs. The highly conductive PEEK membrane exhibited good membrane integrity. The flexible IR-VEDs exhibited superior IR adjustment ability and excellent cycling stability.